THE ROLE OF TRUST IN MEDIATING BRAND AMBASSADOR AND BRAND AWARENESS TOWARDS PURCHASE DECISIONS - Christiana, Irma; Hasibuan, Nasywasuri (Jurnal Manajemen, 2024)
This research aims to identify variables that can influence purchasing decisions mediated by trust. This research approach is quantitative-descriptive. Sampling used a purposive sampling method to achieve a sample size based on the Lemeshow formula. Data collection was carried out by distributing questionnaires in the form of a Google Form. The data analysis technique uses the Partial Least Squares Structural Equation Model (PLS-SEM). Hypothesis testing shows that brand ambassadors and brand awareness influence trust and purchasing decisions. Trust is able to mediate the influence of brand ambassadors and brand awareness on purchasing decisions.